Kepastian Hukum Terhadap Putusan Peradilan Adat Aceh dalam Penyelesaian Tindak Pidana Pencurian - Khairul Riza; Irpan Husein Lubis; Nicha Suwalla (Penerbit Goodwood, 2022)
Purpose: The purpose of writing this journal is to find out the authority of the customary court in resolving criminal acts of theft, to find out the factors that cause the keuchik's decision to have no legal certainty, and to find out the obstacles and efforts to resolve crimes that were resolved by the keuchik through customary justice. Methodology: The method used is empirical juridical research, namely research through a series of field interviews with respondents and informants. Results: The results of the study show that, the authority of customary justice in resolving criminal acts of theft is in accordance with what is stipulated in Qanun Number 9 of 2008 against light-scale theft crimes involving the residents of the gampong concerned, but sometimes also against heavier scale theft crimes. Limitations: Obstacles to the settlement of criminal acts resolved by the keuchik through customary justice, namely the difficulty of uniting good opinions between conflicting parties, obstacles to the bureaucratization of customary courts that depend on the government, lack of socialization of customary justice by the government to the community, and lack of coordination with other law enforcement agencies in conventional justice system. Contribution: The efforts made to overcome these obstacles are increasing the socialization of customary justice, strengthening the capacity of traditional justice personnel and institutions, building cooperation between institutions and the commitment and seriousness of the Regional Government in supporting the implementation of customary justice.